Los Dorados de la Revolución de Independencia : proyectos e innovaciones en la minería antioqueña (2015)
ABSTRACT:In the New Kingdom of Granada, particularly during the last decades of the colonial period, some projects for promoting mining were carried out at different levels. In a province rich in gold as Antioquia, that Project-ism was evident. In times of the Independence Revolution that project-ism remained. However, the initiatives were not made by representatives of the Spanish Monarchy but by “criollos”, who betted on the development of a particular idea of nation. Such interest was present in some elite groups of the province that succeeded in developing significant progress in the gold mining in the XIX century. The aim of this article is to show the continuity between the attempts of promoting and modernising mining in the XIX century, in comparison with those of the revolutionary times and the ones of the late XVIIIth century. This is particularly ignored Antioquia’s mining historiography and can be demonstrated with concrete examples by using primary sources from that time. Keywords: Mining, bourbon reforms, revolution, independence, techniques.